PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN KOSMETIK YANG MELANGGAR STANDART BPOM - Dicky Celfin Wahyudi; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
Currently, beauty product trends are rising rapidly among the public, leading to the emergence of rogue players in the cosmetics industry. A cosmetic product license is essential as it ensures that the product is safe to use with government approval. The aim of this study is to evaluate the safeguarding of consumers against the spread of beauty products that contain dangerous components which do not meet the BPOM standards, and to determine the accountability of economic agents for the distribution of harmful cosmetics. The research was carried out by utilizing interview and documentation methods and analyzed through qualitative data analysis techniques. Consequently, the law protects consumers under the Consumer Protection Act No. 8 of 1999 and Indonesian National Agency for Drugs and Food Control regulations No. HK. 4.17.45 for cosmetics. Economic agents are liable for compensating or replacing goods for the distribution of cosmetic products that cause harm to consumers. If fraudulent activity is identified, economic agents may face penalties, depending on the extent of the manufacturer's negligence and the level of damage incurred by the consumer. Such penalties may include fines or imprisonment, and the severity of these sanctions is based on the level of negligence exhibited by the manufacturer and the loss suffered by the consumer.